Efficacy and safety of Bacteroides fragilis BF839 for pediatric autism spectrum disorder: a randomized clinical trial - Lin, Chu-hui; Zeng, Ting; Lu, Cui-wei; Li, De-yang; Liu, Yi-ying; Li, Bing-mei; Chen, Sheng-qiang; Deng, Yu-hong (Frontiers in Nutrition, 2024)
Background The clinical utility of Bacteroides fragilis in treating autism spectrum disorder (ASD) remains unclear. Therefore, this randomized, double-blind, placebo-controlled study aimed to explore the therapeutic effects and safety of B. fragilis BF839 in the treatment of pediatric ASD. Methods We examined 60 children aged 2–10 years diagnosed with ASD, and participants received either BF839 powder (10 g/bar with ≥106 CFU/bar of viable bacteria, two bars/day) or placebo for 16 weeks. The primary outcomes was Autism Behavior Checklist (ABC) score. The secondary outcomes were Childhood Autism Rating Scale (CARS), Social Responsiveness Scale (SRS), Normal Development of Social Skills from Infants to Junior High School Children (S-M), Gastrointestinal Symptom Rating Scale (GSRS) scores, and fecal microbiome composition. Assessments were performed on day 0 and at weeks 8 and 16. Results Compared with the placebo group, the BF839 group showed significant improvement in the ABC body and object use scores at week 16, which was more pronounced in children with ASD aged <4 years. Among children with a baseline CARS score ≥30, the BF839 group showed significant improvements at week 16 in the ABC total score, ABC body and object use score, CARS score, and GSRS score compared to the placebo group. Only two patients (6.67%) in the BF839 group experienced mild diarrhea. Compared with baseline and placebo group levels, the BF839 group showed a significant post-intervention increase in abundance of bifidobacteria and change in the metabolic function of neuroactive compounds encoded by intestinal microorganisms. Conclusion BF839 significantly and safely improved abnormal behavior and gastrointestinal symptoms in children with ASD.